2014
DOI: 10.1016/j.bmc.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Development of inhibitors of heterotrimeric Gαi subunits

Abstract: Heterotrimeric G-proteins are the immediate downstream effectors of G-protein coupled receptors (GPCRs). Endogenous protein guanine nucleotide dissociation inhibitors (GDIs) like AGS3/4 and RGS12/14 function through GPR/Goloco GDI domains. Extensive characterization of GPR domain peptides indicate they function as selective GDIs for Gαi by competing for the GPCR and Gβγ and preventing GDP release. We modified a GPR consensus peptide by testing FGF and TAT leader sequences to make the peptide cell permeable. FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 70 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…In the years since, a growing body of work by us and others indicates that genetic or epigenetic factors that deregulate the intricate network of "accessory proteins" in a variety of disease states are just as significant as those that directly affect the G proteins and GPCRs, if not more so. 7,[12][13][14] Non-canonical G protein signaling by GEMs; The serendipitous discovery of a family of proteins based on homology to a synthetic peptide…”
mentioning
confidence: 99%
“…In the years since, a growing body of work by us and others indicates that genetic or epigenetic factors that deregulate the intricate network of "accessory proteins" in a variety of disease states are just as significant as those that directly affect the G proteins and GPCRs, if not more so. 7,[12][13][14] Non-canonical G protein signaling by GEMs; The serendipitous discovery of a family of proteins based on homology to a synthetic peptide…”
mentioning
confidence: 99%
“…Recently, Appleton et al identified small molecule GDIs which weakly inhibit Gα subunits at high micromolar concentrations while maintaining intact the stimulation of the Gβγ signaling [21]. In the present study, we have designed, synthesized and profiled the effects of four compounds (9a, 9b, 13 and 14) on the migration of selected cancer cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, we have designed, synthesized and profiled the effects of four compounds (9a, 9b, 13 and 14) on the migration of selected cancer cell lines. These compounds were designed based on compound 12 (ketamine 9827), the more synthetically tractable compound, as disclosed by Appleton et al [21]. At this time, there is no suitable crystal structure of Gα i 2 that can be used for our purpose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations